Anthropometric data as predictors of obstructive sleep apnea severity - Pinto,José Antonio (2011)
The Obstructive Sleep Apnea Syndrome is a chronic disease characterized by episodes upper airway collapse, and has been associated with increased cardiovascular morbidity. AIM: To correlate the neck, abdominal and pelvic circumference with the AHI and oxyhemoglobin saturation in OSA patients, and to correlate these values with disease severity. MATERIALS AND METHODS: A prospective descriptive study of 82 patients evaluated complaints suggesting OSA, from July 2008 to March 2010. All patients underwent polysomnography, an ENT clinical exam, measures of the BMI, abdominal, pelvic, and cervical circumferences. The mean, standard deviations and Spearman's correlations were analyzed. RESULTS: The mean AHI in men was 39 events/hr; in women it was 21 events/hr in women. The mean neck circumference was 34. 5 cm in women and 41. 3 cm in men, the mean abdominal circumference was 94. 3 cm in women and 101. 5 cm in men, and the pelvic circumference was 105. 7 cm in men and 108. 7 cm in women. The neck circumference correlated more closely to the AHI in men (r=+0. 389 p=0. 001). The relationship between the abdominal circumference correlated more with AHI than with the BMI in men (AbC r=+0. 358 p=0. 003 BMI r=+0. 321 p=0. 009). CONCLUSIONS: The neck circumference is the best anthropometric measurement of respiratory disorder severity compared to the AbC or the BMI